2005
DOI: 10.1111/j.1744-7429.2005.04040.x
|View full text |Cite
|
Sign up to set email alerts
|

Crop Size and Fruit Neighborhood Effects on Bird Visitation to Fruiting Schefflera morototoni Trees in Puerto Rico1

Abstract: Studies of zoochorous seed dispersal systems often consider crop size, yet seldom consider the kinds and amounts of fruits surrounding parent plants (the fruit neighborhood) when attempting to explain among-plant variation in fruit removal. We studied avian frugivory at 24 Schefflera morototoni trees from February to May 1998 in central Puerto Rico. The number of fruits removed by avian seed dispersers per visit was similar among focal trees (typically 2-4). In contrast, visitation rate was highly variable (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
121
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(127 citation statements)
references
References 48 publications
(76 reference statements)
3
121
1
2
Order By: Relevance
“…Rudgea viburnoides and Miconia staminea belong to the two most important families of plants for tropical frugivorous birds (Rubiaceae and Melastomataceae, respectively) and, because their fruits are succulent, they are appreciated by a variety of frugivorous birds, especially the small ones that feed in the lower strata of the vegetation (Snow 1981, Maruyama et al 2013). On the other hand, the fruit of Schefflera morototoni is rich in lipids and proteins (Snow 1971), and therefore also attracts a wide variety of frugivores ranging from the smallest to the largest (Saracco et al 2005, Parrini et al 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rudgea viburnoides and Miconia staminea belong to the two most important families of plants for tropical frugivorous birds (Rubiaceae and Melastomataceae, respectively) and, because their fruits are succulent, they are appreciated by a variety of frugivorous birds, especially the small ones that feed in the lower strata of the vegetation (Snow 1981, Maruyama et al 2013). On the other hand, the fruit of Schefflera morototoni is rich in lipids and proteins (Snow 1971), and therefore also attracts a wide variety of frugivores ranging from the smallest to the largest (Saracco et al 2005, Parrini et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Frugivorous birds represent 56% of the world's avian families and, in Neotropical forests, 25 to 30% of the avifauna includes fruits in their diet (Pizo & Galetti 2010). According to Jordano (1987), studies of frugivory by birds in tropical forests are relatively well reported (e.g., Snow 1981, Jordano 1987, Galetti & Pizo 1996, Medellín & Gaona 1999, Silva & Tabarelli 2000, Bascompte et al 2003, Saracco et al 2005. It is estimated that 50 to 90% of tree species in tropical forests produce zoochorous fruit (Howe & Smallwood 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Fruit production is continuous with prolonged maturation, though annual fruit volume and maturity may be influenced by climatic factors (Franco and Ferreira 2002). Infructescences are abundant, green-purplish, and occur at the ends of branches, this provides contrast with the leaves and make it easier for the birds to locate those (Saracco et al 2005). Fruits are fleshy drupes with an average width of 4-6 mm and average length 6-10 mm.…”
Section: Introductionmentioning
confidence: 99%
“…They usually contain two flat seeds each up to 5 mm in length and with a < 1 mmthick protein-and lipid-rich pulp covering (Snow 1971). They are considered an important food source for forest birds throughout the plants Central and South America range (Snow 1981;Sick 1997;Saracco et al 2005;Parrini et al 2013). Given the above, our objectives were: (i) to record the species of birds that consumed Schefflera morototoni fruits; and (ii) to evaluate the potential of these species as dispersers of seeds from this plant species in a Cerrado-Amazon Forest transition area in the state of Mato Grosso, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…A fair number of field studies document how fruiting plant neighbors affect fruit-removal rates by creating facilitation or competition among plant neighbors that share frugivores (Manasse and Howe 1983, Sargent 1990, Garcı´a et al 2001, Carlo 2005, Saracco et al 2005, Blendinger and Villegas 2011. As far as we are aware, there are no empirical studies examining how seed dispersal distances are affected by neighborhood and crop size variables, or probing on the effects of neighborhood-mediated dispersal on plant population dynamics.…”
Section: Introductionmentioning
confidence: 99%